Estimation of the Influence of Operational Factors on the Oxygen Content of the Turbine Condensate at the Outlet from the Condenser of Steam Turbine - Shempelev A. G.; Iglin P. V.; Sushchikh V. M. (Problems of the Regional Energetics)
The aim of the article is to analyze the influence of different factors on the oxygen content in the condensate using the example of the condenser of the steam turbine unit T-110/120-130. For the first time, the authors of the article analyze in details how the basic parameters of the condenser's operation (the condenser heat load, the flow and temperature of the cooling water, the air inflow in the condenser, the condition of the heat exchange surface) influence the oxygen content of the condensate. The authors come to the conclusion that with standard air inflow in the vacuum system, the equilibrium oxygen content, which corresponds to the norms in the condensate at the condenser outlet, is only possible in its operation modes when the steam flow to the condenser is more than 50% of the nominal flow and cooling water temperatures are equal to or greater than calculated for this type of condenser. The conclusions are confirmed by the experimental material. The results of the research are the basis for the development of measures aimed to increase the deaerating capacity of condensers depending on specific operating conditions.